A comparative study of two different weighted vests and its effect on attention span in children with attention deficit hyperactive disorder - Dr. GRACE LYDIA SAROJINI; JOHNISH ABRAHAM (International Journal of Pharma and Bio Sciences, 2017)
ADHD is characterized by developmentally inappropriate impulsivity, inattention, and hyperactivity This study describes the comparison about the effect of two different weighted vests and its increase on attention span in children with ADHD .This is a quantitative research model and convenient sampling procedure was done for the study. Twenty children with ADHD of age group of five to seven years and both genders were used for this study. Vanderbilt ADHD diagnosing parent rating scale (VADPRS) was used for screening. Twenty students with documented attention difficulties and hyperactivity were timed with a stopwatch to measure their on-task behavior during fine motor activities in the clinical setup. The results shows that There is a statistical significance difference between 5% and 10% weighted vest in the Attention span at 95% [P <0.05].These preliminary findings support the hypothesis that wearing of increased weighted vest (10% of body weight) to apply deep pressure increases the task behavior than 5% of weighed vest during fine motor activities.